A Bilingual 'Morisco Qur'an' with Thirteen Lines to the Page. Issue 3 (October 2017) - Martínez de Castilla, Nuria
Abstract : Three copies of the 'Morisco Qur'an', RESC/101D.2, RESC/39E, and RESC/58B.1, provide an exceptional testimony for the study of textual transmission within Morisco communities. They lead us to think that the copyists working for these communities knew and used a systematic methodology for transcribing texts which we could call 'commented' (or 'translated') Qur'ans, with 13 lines to the page. In all three cases, the text was written at the beginning of the sixteenth century, if not in direct parallel at least within a short time span, by the same hand, with an identical layout, on a paper of the same type and size, and with the same portions of text on the same page. They are clearly exceptional, since no similar examples have been found in the entire manuscript production of the Western Islamic world known to date. We are dealing here with a careful process of standardisation similar to that found later in the wider Islamic world––more precisely in the Ottoman Empire––from 1620 onwards, which will become widespread in the eighteenth and nineteenth centuries.